Impact of Urbanization on Environmental Eminence: Moderating Role of Renewable Energy - Kusiyah, Kusiyah; Mushtaq, Mansoor; Ahmed, Shabbir; Abbas, Ansar; Fahlevi, Mochammad (International Journal of Energy Economics and Policy, 2024)
In the era of modernization, the movement of the multitude from rural to urban regions all over the globe is rising swiftly. This movement crafts so many socio-economic prospects for the masses. However, in chorus, it has made severe challenges for the eminence of the environment due to a decrease in forestation and the arrangement of more buildings and plants, causing CO2 emissions. It is unmanageable to edge the endurance of urbanization, and the issue is how we can switch its adversative effects on the environment. This study investigated the moderating role of renewable energy consumption in the urbanization-CO2 nexus. For this study, twenty-three of the most urbanized economies from around the world were chosen from 1997 to 2021. Three econometrics techniques are applied for empirical investigation: fixed effect model, robust least square and panel quantile regression with twelve model specifications. The dependent variable is carbon dioxide (CO2) emissions. The explanatory variables are gross fixed capital formation, patent application, inflation, financial development, industrial growth, urbanization and interaction term of renewable energy and urbanization. To check the robustness of empirical findings, we used four different proxies of (CO2) emissions and three different proxies of urbanization. In our empirical findings, patent application, inflation and industrial growth are positively and significantly associated with all proxies of CO2 emissions. While financial development is inversely and significantly allied with CO2 emissions. The impact of all proxies of urbanization is positive and significant on CO2 production. But the moderating effect of renewable energy on environmental depredation is inverse and significant. It suggests using clean and renewable energy and developing the financial sector to improve the eminence of the environment. Our research aligns with the sustainable development goals and the corporate social responsibility stream, making some valuable contributions to the body of previously established research.